Generation of a Ym1 deficient mouse utilising CRISPR-Cas9 in CB6 embryos - J. E. Parkinson; G. E. Baldwin; P. H. Papotto; N. E. Humphreys; A. J. Day; A. D. Adamson; J. E. Allen; T. E. Sutherland (Transgenic Research, 2025)
Chitinase-like proteins (CLPs) are of wide interest due to their significant roles during both homeostatic and pathological processes. Human CLPs such as YKL-40 have been proposed as biomarkers of disease severity in many conditions. Murine CLPs Brp39, Ym1, and Ym2 are similarly upregulated in multiple mouse models of pathology. Investigation of Ym1 and Ym2 is hampered by recent gene duplication events on the C57BL/6, but not BALB/c, background leading to complexity in the genomic locus. Here, we have generated a Ym1 deficient mouse using a novel CRISPR-Cas9 targeting approach involving CB6 (C57BL/6 X BALB/c) mixed background embryos. Validation using flow cytometry, ELISA, and immunofluorescence confirmed no expression of mature Ym1 protein. Additionally, expression of related genes including Chia, Chil1, and Chil4 were not altered in Ym1-deficent animals. This new transgenic mouse line will be key for future investigations of CLP functions and the utilised approach to genetic manipulation may provide a useful strategy for other genes which show differences in copy number between inbred mouse strains.